HUBUNGAN PENDAPATAN ORANG TUA TERHADAP HASIL BELAJAR SISWA PASCA PANDEMI COVID 19 DI KELAS IV SD NEGERI 10 BANDA ACEH - Iqbal, Muhammad; Isa, Muhammad; Maulidar, Maulidar (Jurnal Seramoe Education, 2025)
This research was conducted to see the relationship between parental income and student learning outcomes at SDN 10 Banda Aceh City. In this research, educational success can be seen through the learning outcomes achieved by students after carrying out the learning process. Minimum Completeness Criteria. (KKM) that has been determined. Someone with high learning outcomes can be said to have been successful in learning. From the results of the analysis that has been carried out regarding the relationship between parental income and student learning outcomes at SDN 10 Banda Aceh City, it can be concluded that, the income of parents of class IV students at SDN 10 Banda Aceh was measured using a questionnaire that was distributed. From the results obtained, the income of parents of class IV students at SDN 10 Banda Aceh was 30% very high income, 10% high income, 55% medium income and 5% low income. From these results it can be said that the income of the parents of class IV students at SDN 10 Banda Aceh is medium income. Then, the learning outcomes of class IV students at SDN 10 Banda Aceh were measured using final semester grades with a KKM limit of 70. Of the 20 students, all of them completed and got scores exceeding the KKM. The correlation test that has been carried out shows the results that Ha is accepted and Ho is rejected. So there is a positive relationship between parental income and the learning outcomes of class IV students at SDN 10 Banda Aceh. This shows that parental income has a relationship with learning outcomes, the higher parental income will have an impact on increasing student learning outcomes.